Morphological Changes in Subcutaneous White Adipose Tissue After Severe Burn Injury. Issue 2 (March 2016) - Saraf, Manish Kumar; Herndon, David N.; Porter, Craig; Toliver-Kinsky, Tracy; Radhakrishnan, Ravi; Chao, Tony; Chondronikola, Maria; Sidossis, Labros S.
Abstract : Severe burn injury produces a plethora of metabolic abnormalities which contribute to the prolonged morbidity of burn survivors. The authors have recently demonstrated trans-differentiation of white adipose tissue (WAT) after burn trauma, toward a more thermogenic phenotype. However, the impact of burn injury on subcutaneous WAT (sWAT) morphology in humans is unknown. Here, the authors studied the effect of severe burn injury on the architecture of sWAT. sWAT was collected from 11 severely burned children (11 ± 3 years; 55 ± 16% total BSA burned) and 12 nonburned healthy children (9 ± 3 years). Histology, electron microscopy, immunohistochemistry, and immunofluorescence were performed on fixed adipose tissue sections. sWAT cytokine and collagen concentrations were measured by multiplex assay and sirius/fast green staining method, respectively. sWAT histology demonstrated multiple fat droplets, significantly ( P < .05) reduced mean cell size (104 ± 6 vs 68 ± 3 μm) and higher collagen content (7 ± 0.8 vs 4 ± 0.4) in burn patients. sWAT from burn victims stained positive for CD68 suggesting infiltration of macrophages. Furthermore, electron microscopic analysis showed multiple fat droplets and greater mitochondrial abundance in sWAT of burn survivors. In agreement with this, mitochondrial respiratory capacity in the leak and coupled state increased by 100% in sWAT of burned children from 1 to 3 weeks postinjury. The cytokines IL-6, IL-8, IL-13, IL-1a, IL-1b, MCP-1, and TNF-α were all significantly greater in the sWAT of burned children versus healthy children ( P < .05). Furthermore, IL-6, IL-8, IL1-a, IL-1b, and TNF-α significantly increased after injury in sWAT of burned children ( P < .05). This study provides detailed evidence of morphological and functional changes in sWAT of burn survivors which was associated with tissue inflammation. A better understanding of morphological and functional changes in sWAT will help discern the mechanisms underlying hypermetabolism in burned patients.